Ekologi Politik Nikel: Transformasi Ruang Hidup dan Konsekuensi Sosial di Halmahera Tengah - Andi Sumar Karman; Pawennari Hijjang; Ahmad Ismail (Universitas Andalas, 2026)
Nickel has become a central pillar of Indonesia’s extractive economy amid the global energy transition. Following the 2020 downstream industrialization policy, the expansion of nickel mining and smelter industries has accelerated socio-ecological transformation in eastern Indonesia. This study examines how the conversion of agrarian–coastal landscapes into industrial zones reshapes livelihoods, ecological relations, and social structures in Lelilef Waibulan Village, Central Halmahera, the site of the Indonesia Weda Bay Industrial Park (IWIP). Using a critical ethnographic approach, fieldwork was conducted from April to December 2025 through participant observation, semi-structured interviews with 45 informants, and document analysis. Findings reveal significant ecological degradation and growing social inequality. At least 7,000 hectares of productive land, including secondary forests, coconut groves, and mixed gardens, have been converted into industrial infrastructure. Residents reported severe water turbidity, declining fish catches, coastal sedimentation, and the disappearance of several freshwater sources. Among 31 observed households, 45 had shifted from farming and fishing to precarious wage labor in the mining sector, characterized by temporary contracts and economic insecurity. The study also found widening social disparities between households connected to mining-related economic networks and those excluded from industrial access. Simultaneously, customary rituals and ecological practices tied to ancestral forests and coastal spaces have gradually disappeared due to restricted access and territorial enclosure by corporate concessions. These findings demonstrate that nickel industrialization produces not only environmental degradation but also social dislocation, dependency, and the erosion of local ecological knowledge. The study argues that Indonesia’s extractive development model reproduces uneven development in which economic growth is accompanied by ecological vulnerability and new forms of exclusion.